2010
DOI: 10.1007/s00404-010-1759-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of Helicobacter pylori in the pathogenesis of hyperemesis gravidarum

Abstract: Screening for H. pylori should be added to the investigations of hyperemesis gravidarum cases. Non teratogenic treatment can be considered in intractable cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(35 citation statements)
references
References 13 publications
2
29
0
3
Order By: Relevance
“…6,22,40 Kuscu and Koyuncu, suggested that NVP beyond the second trimester are indicative of H. Pylori infection and other studies reported that the severity of NVP experienced correlated with the density of H. Pylori. 29,40 Maternal diet, during pre-conception and in pregnancy is associated with the incidence and severity of NVP.…”
Section: External Factorsmentioning
confidence: 94%
See 1 more Smart Citation
“…6,22,40 Kuscu and Koyuncu, suggested that NVP beyond the second trimester are indicative of H. Pylori infection and other studies reported that the severity of NVP experienced correlated with the density of H. Pylori. 29,40 Maternal diet, during pre-conception and in pregnancy is associated with the incidence and severity of NVP.…”
Section: External Factorsmentioning
confidence: 94%
“…6,11 Hormones associated with pregnancy and possibly NVP and HG include hCG, thyroxine, progesterone and oestrogen but psychological, genetic and external risk factors such as smoking, age, infection and diet are also implicated. 2,16,[17][18][19][20][21][22] Discretionally, these implicated causes are hereby briefly reviewed under five basic points:…”
Section: Nausea and Vomiting In Pregnancy And Hyperemesis Gravidarummentioning
confidence: 99%
“…Hyperemesis gravidarum [8][9][10][11][12] Preeclampsia [13][14][15]23] Iron-deficiency Anemia [16][17][18][19] Intrauterine growth Restriction [20][21][22]27] Spontaneous abortion [24][25][26] and inflammatory damage over the gastric epithelium resulting in gastrointestinal disturbance such as hyperemesis gravidarum. H. pylori sequesters essential micronutrients from the host organism such as Iron (Fe) and it causes iron deficiency anemia.…”
Section: Referencementioning
confidence: 99%
“…This particular complication affects 0.3% to 2.0% of all pregnancies. The reason to suffer from hyperemesis gravidarum is unknown, but hypotheses include hormonal mechanisms, emotional factors and H. pylori infection [8].…”
Section: Hyperemesis Gravidarum (Hg)mentioning
confidence: 99%
“…Empfehlungen zur konsequenten Therapie der Helicobacter-pylori-Infektion in der Schwangerschaft bei HG gegeben werden [46]. In jedem Fall geben die Studienergebnisse Anlass, bei Versagen der üblichen Therapien nach einer solchen Infektion zu suchen und zumindest bei therapierefraktären Beschwerden, bei serologisch, bioptisch oder mittels 13C-Harnstoff-Atemtest-gesicherter Helicobacter-pyloriInfektion, einen Therapieversuch durchzuführen [47]. Als Therapieoptionen stehen Kombinationstherapien aus Protonenpumpenhemmern (Omeprazol) und Antibiotika (Clarithromycin, Amoxicillin, Metronidazol) zur Verfügung (l " Tab.…”
Section: Helicobacter Pyloriunclassified